+0  
 
0
62
1
avatar

Find the value of x and y. 

(y-2)/3      =    (1-5x)/(y-4)     =      24/(y-1)

 

Thanksss! 

 Jan 19, 2021
 #1
avatar+8456 
0

We first focus on the first and last part of the equality.

 

(y - 2)/3 = 24/(y - 1)

(y - 2)(y - 1) = 72

y^2 - 3y + 2 - 72 = 0

y^2 - 3y - 70 = 0

(y - 10)(y + 7) = 0

y = 10 or y = -7

 

Case 1: y = 10

Then (10 - 2)/3 = (1 - 5x)/(10 - 4).

i.e., (1 - 5x)/6 = 8/3

(1 - 5x) = 16

x = -3

 

So (x, y) = (-3, 10) is a solution.

 

Case 2: y = -7

Then (-7 - 2)/3 = (1 - 5x)/(-7 - 4)

i.e., 1 - 5x = 33

x = -32/5

 

So (x, y) = (-32/5, -7) is another solution.

 Jan 19, 2021

50 Online Users

avatar
avatar